Effective production of recombinant Δ60VP1 chicken anemia virus protein in Escherichia coli and its application to a serodiagnostic indirect ELISA - Saruda Wanganurakkul (2020)
© 2020 Elsevier B.V. Chicken anemia virus (CAV) causes severe anemia and immunosuppression in chickens. VP1 is the main capsid protein, and is suitable for diagnostic kit development, however, it has 24 arginine residues in the first forty N-terminal amino acids of the protein causing toxicity to bacteria leading to reduced prokaryotic expression. In this study, a 60 amino acid N-terminally truncated VP1 (Δ60VP1) which removes the toxic region was expressed in Escherichia coli and the resultant insoluble recombinant protein was purified by Ni-NTA affinity chromatography with anionic denaturing detergents. The high amounts of purified Δ60VP1 produced (150 mg/L) retained appropriate antigenicity and the antigen was used to develop an indirect enzyme-linked immunosorbent assay (ELISA) for serological diagnosis of CAV. One hundred fifty-two chicken serum samples (n = 152) were evaluated using the newly developed Δ60VP1 indirect ELISA (cutoff value = 7.58 % S/P). The sensitivity and specificity of the Δ60VP1 indirect ELISA were 87.50 % and 95.31 %, respectively, while the agreement between the Δ60VP1 indirect ELISA and the commercial IDEXX CAV ELISA was 90.79 % (kappa = 0.814). In this study, we have developed an alternative VP1 production platform in E. coli by truncating the N-terminal 60 amino acids (Δ60VP1) and using anionic denaturing detergents during the purification to successfully solubilize the insoluble Δ60VP1. The antigen was purified with high yield and good immunoreactivity, and an indirect ELISA was developed. The assay could potentially be applied to large-scale CAV serosurveillance.